Daya Dukung dan Jasa Lingkungan Taman Keragaman Hayati dalam Penurunan Emisi Gas Rumah Kaca Serta Rosot Karbon - A Hadian Pratama Hamzah; Nurhasanah Nurhasanah; Cicik Suriani; Sohifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to assess carbon stock potential and carbon sequestration as part of environmental services contributing to carbon emission reduction in Kiarapayung Biodiversity Park. The method applied was a Permanent Sample Plot (PSP) design modified from and integrating the Indonesian National Standard (SNI) 7724:2011 and the Rapid Carbon Stock Appraisal (RaCSA) method developed by ICRAF Southeast Asia. Measurements and calculations were conducted on five carbon pools using a combined approach, consisting of a census-based method for aboveground biomass assessment and a sampling-based method for the remaining four carbon pools. The results indicate that the average carbon potential in Kiarapayung Biodiversity Park was 68.18 ton ha⁻¹, equivalent to 250.22 ton CO₂e ha⁻¹. Block 6 recorded the highest carbon stock at 157.02 ton ha⁻¹ (576.25 ton CO₂e ha⁻¹), followed by Block 7 and Block 2 with carbon stocks of 77.23 ton ha⁻¹ (283.43 ton CO₂e ha⁻¹) and 60.74 ton ha⁻¹ (222.92 ton CO₂e ha⁻¹), respectively. Lower carbon potentials were observed in Blocks 8, 3, 5, and 1, ranging from 55.47 to 43.75 ton ha⁻¹ or equivalent to 203.59–222.92 ton CO₂e ha⁻¹. Blocks 1 and 5 exhibited the lowest carbon potentials, amounting to 41.84 and 34.97 ton ha⁻¹ or equivalent to 128.33 and 153.56 ton CO₂e ha⁻¹, respectively. In conclusion, Kiarapayung Biodiversity Park serves not only as a conservation area but also has considerable potential to be developed as a forest- and carbon-based ecotourism and edutourism site. Such development may be supported through digital carbon data utilization using QR codes, appropriate species selection, educational games and quizzes related to carbon data, integration of carbon economic value into environmental service payment mechanisms, and the establishment of a living laboratory focused on carbon research. Keywords: Greenhouse Gas Emissions, Environmental Services, Carbon, Conservation, Biodiversity Park